The Dynamics of Islamic Law in the Balkans: Husein Dozo's Renewal Thoughts - Yusdani, Yusdani; Arfaizar, Januariansyah; Arifai, Ahmad (Madania: Jurnal Kajian Keislaman, 2023)
This article examines the dynamics of Islamic legal thought in the Balkans with a focus on the thoughts of a Muslim modernist and reformer Husein Dozo (1912-1982). He is one of the most prominent Bosnian Muslim scholars of the last two hundred years. Hussein Dozo was born at a time when the many challenges the Balkan Muslim world is experiencing are so complex and overwhelming. Therefore, it is on that basis that Husein Dozo offers his main idea to reinterpret Islamic teachings which are intended for the younger generation of Muslims. This study uses qualitative research methods that are presented descriptively using theological and sociological approaches. Hussein Dozo was a native Balkan Muslim scholar who was well aware of the impact of modernity on Islamic legal traditionalism. At a time when scholars were discriminated against for their thoughts and beliefs, Hussein Dozo tried to provide space through seminars to introduce that religious activities have broad benefits. He also gave a fatwa regarding the collection and distribution of zakat that can be managed by zakat institutions with the aim of people's welfare. Through zakat, Hussein Dozo was able to alleviate poverty and intellectual decline in the Balkans. Artikel ini mengkaji dinamika pemikiran hukum Islam di kawasan Balkan dengan fokus pemikiran seorang modernis dan reformis muslim Husein Dozo (1912-1982). Tokoh ini merupakan seorang cendekiawan Muslim Bosnia paling menonjol dalam dua ratus tahun terakhir.  Husein Dozo lahir pada saat banyaknya tantangan yang dialami dunia Muslim Balkan yang begitu kompleks dan luar biasa. Oleh karena itu, atas dasar itulah husein Dozo menawarkan gagasan utamanya untuk menafsirkan kembali ajaran Islam yang diperuntukan bagi generasi muda muslim. Kajian ini menggunakan metode penelitian kualitatif yang disajikan secara deskriptif menggunakan pendekatan teologi dan sosiologi. Pada penelitian ini ditemukan bahwa Husein Dozo adalah seorang cendekiawan Muslim asli Balkan yang sangat menyadari dampak modernitas terhadap tradisionalisme hukum Islam. Di saat para cendekiawan mendapat diskriminasi atas pemikiran dan kajiannya, Husein Dozo mencoba memberikan ruang melalui seminar untuk memperkenalkan bahwa kegiatan agama memiliki manfaat secara luas. Ia juga memberikan fatwa mengenai pengumpulan dan pembagian zakat yang dapat dikelola oleh Lembaga zakat dengan tujuan kesejahteraan rakyat. Melalui zakat, Husein Dozo mampu mengentaskan kemiskinan dan kemunduran intelektual di daerah Balkan.